2017
DOI: 10.1111/1475-6765.12192
|View full text |Cite
|
Sign up to set email alerts
|

Constitutional courts as veto players: Lessons from the United States, France and Germany

Abstract: The number of constitutional courts and supreme courts with constitutional review rights has strongly increased with the third wave of democratisation across the world as an important element of the new constitutionalism. These courts play an important role in day‐to‐day politics as they can nullify acts of parliament and thus prevent or reverse a change in the status quo. In macro‐concepts of comparative politics, their role is unclear. Either they are integrated as counter‐majoritarian institutional features… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 47 publications
0
24
1
3
Order By: Relevance
“…Although the range of possible preferences is broad, many influential studies have focused on judges' policy preferences on the same left–right scale that structures party politics in many countries. Judges may either straightforwardly enact those preferences (the attitudinal model: Segal & Spaeth 2002) or may be constrained (the strategic model: Bergara et al 2003; Brouard & Hönnige 2017). These preferences are either inferred from patterns of judicial (dis)agreement, or they are inferred from the position of the actor appointing each judge.…”
Section: Literaturementioning
confidence: 99%
“…Although the range of possible preferences is broad, many influential studies have focused on judges' policy preferences on the same left–right scale that structures party politics in many countries. Judges may either straightforwardly enact those preferences (the attitudinal model: Segal & Spaeth 2002) or may be constrained (the strategic model: Bergara et al 2003; Brouard & Hönnige 2017). These preferences are either inferred from patterns of judicial (dis)agreement, or they are inferred from the position of the actor appointing each judge.…”
Section: Literaturementioning
confidence: 99%
“…Esto debido a constreñimientos de origen, básicamente los mecanismos de selección. Análisis en el mismo sentido concluyen que los órganos constitucionales actúan como veto players condicionales; dicha actuación se encuentra supeditada a variables como la composición ideológica de la corte y los procedimientos legislativos (Brouard y Hönnige, 2017).…”
Section: Los Poderes De Las Cortes Constitucionales: El Estado De La unclassified
“…On the one hand, he found that many scholars ascribe constitutional courts an "important role" in democratic systems (Hönnige 2011: 346). In this perspective, democracies show a strong tendency towards judicialization if these political systems have courts that can nullify laws (Lijphart 1999;Tsebelis 2002;Brouard and Hönnige 2017;Stone 1994). Ran Hirschl (2004: 73) even identified a "global trend toward juristocracy" which is "part of a broader process, whereby political and economic elites, while they profess support for democracy, attempt to insulate policymaking from the vicissitudes of democratic politics".…”
Section: Introductionmentioning
confidence: 99%